Lymphoepithelioma-like hepatocellular carcinoma: a case report with emphasis on the cytological features - Miyasaka, Chika (Int J Clin Exp Pathol, 2017)
Lymphoepithelioma-like hepatocellular carcinoma (LEL-HCC) is a rare distinct histopathological subtype of HCC, which is characterized histopathologically by the presence of abundant lymphocytes around the neoplastic cells, and less than 50 cases have been reported. In this report, we describe the first cytological case of LEL-HCC. A 58-year-old Japanese male had an elevated serum alpha-fetoprotein (AFP) level, and computed tomography scan demonstrated a tumorous lesion with contrast enhancement in the liver, thus, surgical resection was performed. The Papanicolaou smear of the liver tumor demonstrated small clusters and trabeculae of large-sized polygonal cells in a background of an abundance of small lymphocytes. These tumor cells had a rich granular cytoplasm and large centrally located round to oval nuclei containing conspicuous nucleoli. Immunocytochemical analyses revealed that these cells were positive for AFP, glypican-3, and Hep-Par1. Histopathological study demonstrated LEL-HCC. The cytological features of the present case represent both lymphoepithelioma-like carcinoma and conventional HCC. The prognosis of LEL-HCC may be favorable. Therefore, the diagnosis of this type of tumor is important, and a cytological examination can provide useful information for diagnosis of LEL-HCC.